Back Cover: On‐POM Ring‐Opening Polymerisation of N‐Carboxyanhydrides (Angew. Chem. Int. Ed. 7/2021). Issue 7 (4th January 2021) - Soria‐Carrera, Héctor; Franco‐Castillo, Isabel; Romero, Pilar; Martín, Santiago; de la Fuente, Jesús M.; Mitchell, Scott G.; Martín‐Rapún, Rafael
Abstract : Don't let go ! POMlymers (polyoxometalate–peptide hybrids) are biocidal agents that prevent bacterial adhesion and colonisation of surfaces. In their Communication on page 3449, Scott G. Mitchell, Rafael Martín‐Rapún, and co‐workers report an on‐POM polymerisation of  N ‐carboxyanhydrides, which serves as an innovative platform to design hybrid materials with antimicrobial properties.